Primary aortoenteric fistula: is endovascular repair the prime option? A review of the literature - Kehagias, Dimitrios; Mulita, Francesk; Panagiotopoulos, Ioannis; Lampropoulos, Charalampos; Markopoulos, George; Verras, Georgios-Ioannis; Kehagias, Ioannis (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2022)
Primary aortoenteric fistula (PAEF) is a rare entity that demands high clinical suspicion and efficient management in a limited time. The evolution of interventional radiology established endovascular repair (EVAR) as an attractive option. The English literature was searched using the PubMed database with the terms “primary aortoenteric fistula”, “primary aortoduodenal fistula” or “aortoduodenal fistula”, and “endovascular repair” in different combinations. Studies and original articles that described the role and the outcomes of EVAR for primary aortoenteric fistula were included. Fourteen articles with a total of 15 patients with primary aortoenteric fistula who were managed with EVAR were included in our literature review. PAEF is a rare and lethal entity that everyone should be aware of. EVAR is a salvage option and a valuable weapon in our armamentarium. Is EVAR really a “bridge to surgery” or is it the birth pangs of a minimally invasive definite treatment of PAEF?